2009
DOI: 10.1128/jvi.01509-08
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever Virus Can Remain Virulent after Specific Elimination of the Interferon Regulatory Factor 3-Degrading Function of N pro

Abstract: Pestiviruses prevent alpha/beta interferon (IFN-␣/␤) production by promoting proteasomal degradation of interferon regulatory factor 3 (IRF3) by means of the viral N pro nonstructural protein. N pro is also an autoprotease, and its amino-terminal coding sequence is involved in translation initiation. We previously showed with classical swine fever virus (CSFV) that deletion of the entire N pro gene resulted in attenuation in pigs. In order to elaborate on the role of the N pro -mediated IRF3 degradation in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 51 publications
4
109
0
Order By: Relevance
“…Whether restoring the N pro function in the triple mutant GPE Ϫ virus would further enhance its pathogenicity is under current investigation. Previous data suggest that the IRF3-degrading function of N pro may support the pathogenicity of low-and moderately virulent strains but has only little influence on the pathogenicity of highly virulent viruses: mutations to knock out the N pro -mediated IRF3 degradation did not alter the pathogenicity of the highly virulent CSFV strain Eystrup and resulted in only slight attenuation of the moderately virulent vA187-1 virus (43). E rns forms disulfide-linked homodimers and possesses RNase activity (45,50).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether restoring the N pro function in the triple mutant GPE Ϫ virus would further enhance its pathogenicity is under current investigation. Previous data suggest that the IRF3-degrading function of N pro may support the pathogenicity of low-and moderately virulent strains but has only little influence on the pathogenicity of highly virulent viruses: mutations to knock out the N pro -mediated IRF3 degradation did not alter the pathogenicity of the highly virulent CSFV strain Eystrup and resulted in only slight attenuation of the moderately virulent vA187-1 virus (43). E rns forms disulfide-linked homodimers and possesses RNase activity (45,50).…”
Section: Figmentioning
confidence: 99%
“…Comparison of the genomes of the GPE Ϫ vaccine virus and the parent ALD virus revealed 225 nucleotide substitutions and 46 amino acid differences (22), which did not provide any conclusive information on the molecular basis of the attenuation. Numerous reports suggest that the viral proteins N pro , C, E rns , E1, E2, p7, and NS4B may be involved in determining the virulence of CSFV in pigs (7,8,9,10,11,12,13,32,36,37,38,39,40,43,46,54). So far, however, all conclusions on CSFV virulence determinants rely on mutations that result in downregulation of pathogenicity.…”
mentioning
confidence: 99%
“…N pro (A187-1)/D136N showed higher stability than N pro (KPP)/S17P; N61K, although it was described to be defective in mediating IRF-3 degradation . This suggests that the lack of IRF-3 degradation by this TRASH domain mutant is indeed due to the lack of interaction with IRF-3 as described by Ruggli et al (2009) rather than to N pro instability, although a contribution by the latter cannot be excluded.…”
Section: Discussionmentioning
confidence: 77%
“…The KPP/93 strain showed low pathogenicity in pigs. In previous studies, the suppression of IFN-a/b induction by N pro was related to pathogenicity in pigs (Mayer et al, 2004;Ruggli et al, 2009;Tamura et al, 2014), suggesting that inability of KPP/93 N pro to suppress IFN-a/b induction may contribute to the low pathogenicity of the KPP/93 strain in pigs. In the present study, we identified amino acid residues of N pro responsible for the suppression of IFN-a/b induction by N pro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation